THE EFFECT OF TRAINING AND DEVELOPMENT ON PERFORMANCE: A LITERATURE REVIEW - Dalimunthe, Ritha F .; Mulya , Hana Arissa; Pasaribu , Alde; Andreas , Doly Theo (Neraca: Jurnal Ekonomi, Manajemen dan Akuntansi, 2024)
This literature review examines the vital impact of training and development on organizational performance. Employee training and development is a structured approach aimed at enhancing employees' knowledge, skills, and abilities to achieve organizational objectives more efficiently. This process includes providing education, technical training, mentoring, and relevant work experience to employees. Training and development programs can be formal or informal and may encompass a wide range of topics, such as communication skills, leadership, time management, and job-specific technical skills. The primary goal is to boost employees' competencies and qualifications, enabling them to perform their roles more effectively. As noted by Ottawa University, research indicates that organizations investing in employee development experience double the benefits compared to those that do not. Furthermore, 93% of employees tend to stay longer with companies that prioritize their career growth.